2020
DOI: 10.1016/j.ijchp.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Does mindfulness improve inhibitory control in psychotic disorders? A randomized controlled clinical trial

Abstract: Background/Objective : Impaired Inhibitory Control (IC) is a core feature of psychotic disorders and is related with impaired social functioning in people experiencing psychosis. Despite research showing the benefits of mindfulness over IC in the general population, no study has assessed its effects on IC in psychoses. The aim of our study was to assess the effectiveness of a mindfulness-based intervention combined with integrated rehabilitation treatment in a sample of people diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…MBPs teach these foundational skills across the full continuum of wellbeing, from those currently experiencing severe mental health difficulties right through to those who are flourishing ( Crane et al, 2017 , Huppert, 2009 , López-Navarro et al, 2020 , Pardos-Gascón et al, 2021 ). Mindfulness-Based Stress Reduction (MBSR) was developed to help people cope with stress, pain and illness ( Kabat-Zinn, 1990 ) and Mindfulness-Based Cognitive Therapy (MBCT) integrated MBSR and cognitive-behavioural therapy to help people with a history of recurrent depression learn skills to stay well ( Segal et al, 2013 ).…”
mentioning
confidence: 99%
“…MBPs teach these foundational skills across the full continuum of wellbeing, from those currently experiencing severe mental health difficulties right through to those who are flourishing ( Crane et al, 2017 , Huppert, 2009 , López-Navarro et al, 2020 , Pardos-Gascón et al, 2021 ). Mindfulness-Based Stress Reduction (MBSR) was developed to help people cope with stress, pain and illness ( Kabat-Zinn, 1990 ) and Mindfulness-Based Cognitive Therapy (MBCT) integrated MBSR and cognitive-behavioural therapy to help people with a history of recurrent depression learn skills to stay well ( Segal et al, 2013 ).…”
mentioning
confidence: 99%
“…RCT 50 25. (a) López-Navarro et al [ 78 ] (b) López-Navarro et al [ 79 ] RCT ISRCTN52873519 Spain Community rehabilitation centre Integrated rehabilitation treatment and mindfulness-based intervention, n = 26 Integrated rehabilitation treatment, n = 26 1 × 60 min sessions/week for 26 weeks Inhibitory control (SCWT) Psychotic symptoms (PANSS) 2. RCT 50 26.…”
Section: Resultsmentioning
confidence: 99%
“…López-Navarro et al [ 77 ] Encouraged but not required Guided meditation audiotapes No Not recorded N/A 17. (a) López-Navarro et al [ 78 ] (b) López-Navarro et al [ 79 ] Encouraged but not required Guided meditation audiotapes No Not recorded N/A 18. MacDougall et al [ 80 ] Home practice core requirement Not stated No Not recorded N/A 19.…”
Section: Resultsmentioning
confidence: 99%
“…EF contains three distinguishable components (e.g., inhibitory control, working memory and cognitive flexibility) (Diamond and Ling, 2016), and the inhibitory control aspect of EF may play a crucial role in fine motor sports (Jacobson and Matthaeus, 2014), because athletes competing in these sports must maintain extremely high levels of concentration on their targets while also ignoring internal and external distractions (Diamond and Ling, 2016). López-Navarro et al (2020) found that a long-term mindfulness exercise integrated with rehabilitation treatment improved inhibitory control in patients with psychotic disorder. Nien et al (2020) further reported that a five weeks MBI improved participant performance on inhibition-related conditions (i.e., the incongruent condition) of the Stroop task and increased the durations at which participants completed an exhaustion running test, suggesting associations among MBI, EF, and sport performance.…”
Section: Introductionmentioning
confidence: 99%